2023
DOI: 10.1038/s41396-022-01312-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in interactions over ecological time scales influence single-cell growth dynamics in a metabolically coupled marine microbial community

Abstract: Microbial communities thrive in almost all habitats on earth. Within these communities, cells interact through the release and uptake of metabolites. These interactions can have synergistic or antagonistic effects on individual community members. The collective metabolic activity of microbial communities leads to changes in their local environment. As the environment changes over time, the nature of the interactions between cells can change. We currently lack understanding of how such dynamic feedbacks affect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…We found that ZF270 cells in coculture with 1F187 cells had higher alginate lyase activity than ZF270 cells in monoculture. A similar observation has been made in the case of increased expression of chitinases by Vibrio natrigens in response to crossfeeding by Alteromonas macleodii cells (27). We speculate that increased alginate lyase activity combined with competition for oligomeric breakdown products between ZF270 and 1F187 cells causes a shift in the growth dynamics of ZF270 cells (Figure 4).…”
Section: Coexistence With Cross-feeding Cells Shifts the Temporal Gro...supporting
confidence: 84%
See 2 more Smart Citations
“…We found that ZF270 cells in coculture with 1F187 cells had higher alginate lyase activity than ZF270 cells in monoculture. A similar observation has been made in the case of increased expression of chitinases by Vibrio natrigens in response to crossfeeding by Alteromonas macleodii cells (27). We speculate that increased alginate lyase activity combined with competition for oligomeric breakdown products between ZF270 and 1F187 cells causes a shift in the growth dynamics of ZF270 cells (Figure 4).…”
Section: Coexistence With Cross-feeding Cells Shifts the Temporal Gro...supporting
confidence: 84%
“…A possible explanation for how cross-feeder cells influence the growth of degrader cells is through the production or consumption of secreted metabolites(11, 13, 2327). Cross-feeders can decrease the growth of degraders by consuming metabolites that represent nutrients for degraders, thus reducing the availability of these for degraders, or by producing metabolites that inhibit the growth of degraders(26, 28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…144 Microfluidics also allows the analysis of the interactions within communities composed of naturally occurring strains to explore the effects of these interactions on community dynamics. 156,157 For example, a recent study Fig. 4 Microfluidic approaches to quantify the interaction distance among microbial cells.…”
Section: B Cross-feeding and Competition Among Cells In Genetically D...mentioning
confidence: 99%
“…Microbial interactions are inherently dynamic, continuously shaped by their surrounding environment and the intricate interplay among microbes [14, 15]. The competitive exclusion principle of ecology, often referred to as Gause’s Law, asserts that in stable environmental conditions, when two species compete for the same resource, even a slight advantage will eventually result in the dominance of the better competitor, leading to the extinction of the inferior species or its adaptation to a new, non-competitive niche [16].…”
Section: Introductionmentioning
confidence: 99%